Yurisdiksi Dewan Hak Asasi Manusia Dan Intervensi Honor Killing - Mesfer, Salshabilla Alaida; Tahamata, Lucia Charlota Octovina; Leatemia, Wilshen (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Honor Killing is a murder committed to protect family honor. One case of honor killing occurred in Afghanistan in June 2022, where a family member committed an honor killing on two children who had just gone shopping and were returning home. Even though Afghanistan has made various efforts to protect women's human rights, violations of women's rights still occur.Purposes of the Research: To study and find out about the Jurisdictional Arrangements of the Human Rights Council based on International Law and to study and find out whether the Human Rights Council can intervene in acts of Honor Killing in a country.Methods of the Research :This research method is normative juridical where research is carried out by collecting primary, secondary and tertiary data obtained using library research. The data that has been collected is analyzed qualitatively, the description of which is arranged systematically based on legal disciplines to achieve clarity on the issues to be discussed.Results of the Research: The results of this research show that the jurisdictional arrangements of the Human Rights Council based on international law were established as a body under the United Nations (UN) in 2006, through UN General Assembly resolution 60/251. Regulations regarding the Human Rights Council are contained in the UN Charter, which gives the Human Rights Council a mandate to promote and protect human rights throughout the world. In addition, the basic rules and procedures of the Human Rights Council are regulated by the UN Charter, various international human rights instruments, as well as relevant resolutions and decisions of the UN General Assembly. The Human Rights Council has the authority to monitor the implementation of human rights in its member countries, provide recommendations, and investigate human rights violations. The UN Human Rights Council does not have direct authority to carry out physical intervention or law enforcement in certain countries. However, intervention in specific cases such as honor killings depends on a number of factors, including the policy and authority of the board. Direct intervention in cases of individual crimes, including honor killings, falls under the authority of member states and national legal institutions. The Human Rights Council can encourage countries to take firm action in dealing with human rights violations such as